'Export or die': the rise of Brazil as an agribusiness powerhouse. Issue 5 (2nd September 2016) - Andrade, Daniela
Abstract: This article explores the relationship between the rise of Brazil as an agribusiness powerhouse, the country's recent economic upswing and its subsequent crisis. Agribusiness is analysed in the context of the overall dynamics of production, trade and capital flows that have emerged since the neoliberal policy reforms of the 1990s. Statistical series on the country's Balance of Payments (BoP), macroeconomic and sector parameters show that the expansion of agribusiness is part and parcel of a policy-induced phenomenon of primary commodities export specialisation, which conjugates with BoP fragility, the reproduction of debt and external dependence – the core of the current crisis.